Response of dasatinib in different phase of chronic myeloid leukaemia patients - Begum, Moshammat Naznin; Khan, M. A.; Ara, Tasneem; Biswas, Akhil Ranjon; Akter, Mafruha; Islam, M. Manirul; Nazneen, Humayra; Farhad, Muhammad Nurul (International Journal of Research in Medical Sciences, 2024)
Background: Chronic myeloid leukemia (CML) is a stem cell disorder caused by a chromosomal abnormality that results in the formation of the Philadelphia chromosome. This abnormality leads to the production of the Bcr-Abl tyrosine kinase, which drives the uncontrolled proliferation of cells. Imatinib, a tyrosine kinase inhibitor (TKI), revolutionized the treatment of CML, but resistance and intolerance in some patients have necessitated alternative therapies such as Dasatinib, a potent multitargeted inhibitor of Bcr-Abl and Src-family kinases. This study was aims to assess the efficacy and safety of Dasatinib in CML patients who were either newly diagnosed or resistant/intolerant to Imatinib. Methods: A prospective observational study was conducted at Dhaka Medical College & Hospital from July 2016 to June 2017. A total 31 patients with different phases of CML were included in this study. All patients were treated with Dasatinib 100 mg daily and monitored over 12 months. Molecular responses were assessed through quantitative PCR and hematologic responses were evaluated via complete blood counts. Results: Among the 31 patients, two died and two discontinued treatment. Of the remaining 27, 23 (85%) achieved complete hematologic response (CHR), 12 (44%) achieved major molecular response (MMR) and 3 (11%) attained complete molecular response (CMR). All four chronic-phase CML (CML-CP) patients who received Dasatinib as frontline therapy achieved molecular response within one month of starting therapy. Responses were lower in more advanced disease stages, with two blast-phase patients dying. Conclusions: Dasatinib demonstrated significant efficacy and safety in treating CML, particularly in chronic-phase patients and those resistant to Imatinib.